(untitled) (Teaching and Learning Inquiry, 2024)
Positive teacher-student and student-student relationships are among the most significant factors contributing to learning, motivation, wellbeing, and graduation rates in higher education. Trust is commonly understood as a key element for the development and sustenance of positive educational relationships, yet relatively little empirical research investigates trust in higher education classrooms. In this study, we explore how science, technology, engineering and mathematics (STEM) teachers (n=29) from universities in four countries (Canada, New Zealand, Sweden, and USA) describe their intentions and actions related to trust in one of the large enrollment courses they teach. We consider the ways that teachers understand and value trust in their teaching, and what this might suggest about how they approach trust-building with and among their students. We report on four broad approaches to trust expressed by teachers in this study, framed as teacher statements to students: “trust me,” “trust yourself,” “trust each other,” and “I trust you.” This research has implications for teachers, SoTL scholars, and academic developers in higher education. Read the corresponding ISSOTL blog post here.